Cover Image. (18th August 2020) - Wu, Jiali; Mao, Yize; Jiang, Yiquan; Song, Yunda; Yu, Ping; Sun, Shuxin; Li, Shengping
Abstract : The cover image is based on the Original Research Sex differences in solid pseudopapillary neoplasm of the pancreas: A population‐based study by Jiali Wu et al., https://doi.org/10.1002/cam4.3180 .